Correlation between optical absorption redshift and carrier density in phase change materials - Ho, H. W. (2014)
Here, we report an optical absorption redshift map for GeTe-Sb2Te3 pseudo-binary alloys. We found that, with phase change from amorphous to crystalline, the observed redshift increases with Ge concentration along pseudo-line of compositions, which directly reflects the enhanced electron delocalization/resonant bonding and increased carrier concentrations in the respective crystal compounds. The measured valence band maximum shift towards the Fermi energy from amorphous to crystalline phase supports the observed similar trend in redshift and carrier density. We show that the correlation between optical redshift and carrier density, attributed to the resonant bonding, can be rationalized by calculating the valence electron concentration, the ionicity, and hybridization.